Synthesis of eco-friendly bio-based coconut shell magnetic biochar for efficient bisphenol S sequestration in aqueous environment: green technology breakthrough - Katibi, Kamil Kayode; Shitu, Ibrahim Garba; Syahidah Azis, Rabaah; Soo Kien, Chen; Kean Pah, Lim; Awang Kechik, Mohd Mustafa; Md Yunos, Khairul Faezah; Abdulhameed Amusa, Abiodun; Titilayo Katibi, Muibat (Taylor and Francis Ltd., 2024)
Water pollution has emerged as a critical global challenge, particularly the contamination of water bodies with persistent organic pollutants such as Bisphenol S (BPS), a known endocrine disruptor. This study presents the synthesis and application of eco-friendly bio-based coconut shell magnetic biochar (CSMB) for efficient sequestration of BPS from aqueous environments. Utilizing pyrolysis and co-precipitation techniques, the magnetic biochar was characterized through various methods including surface chemistry (pHpzc), electron dispersive X-ray analysis (EDX), Brunauer-Emmett-Teller (BET) N2 adsorption-desorption, scanning electron microscopy (SEM), vibrating sample magnetometer (VSM), and Fourier transform infrared spectroscopy (FTIR). SEM revealed a porous structure with a high surface area, while FTIR confirmed the presence of functional groups essential for adsorption. X-ray diffraction (XRD) and VSM successfully incorporated magnetic nanoparticles, enhancing the separation process post-adsorption. The CSMB demonstrated a significant surface area of 373 m2 g−1, outperforming regular coconut shell biochar (CSB), with a BPS adsorption capacity of 43.5 mg/g compared to 26.7 mg/g for CSB. Batch adsorption tests assessed the impact of operational factors such as initial BPS concentration (8–150 ppm), contact time (30–150 min), temperature (298.15, 318.15, and 338.15 K), pH (3–11), and CSMB dosage (0.1–0.9 g). The results indicated optimal adsorption at pH 6 with a maximum capacity of 52.3 mg/g. Kinetic studies revealed that the pseudo-second-order model best described the adsorption process, while the Langmuir isotherm model provided an excellent fit for the adsorption data. The reusability of CSMB was validated over five cycles, with adsorption capacity decreasing slightly from 43.5 mg/g to approximately 41 mg/g, making it a sustainable and effective adsorbent for water treatment.